Correlation of Hand Washing with Soap of Oxyuris vermicularis Infection in Children at Angkasa Kindergarten, Surakarta - Nadya Putri Oktavia; Adhi Kumoro Setya (Jurnal Biologi Tropis, 2026)
Oxyuriasis is an intestinal worm infection caused by Oxyuris vermicularis, a non-STH (Non-Soil Transmitted Helminths) group, the infection process does not require soil transmission. One way of transmission is through hand to mouth (autoinfection). Preschool aged children are more susceptible to Oxyuris vermicularis worm infection because they tend to be less aware of personal hygiene. The purpose of this study was to determine the relationship between handwashing with soap and Oxyuris vermicularis infection. This research method was observasional analytic with a cross-sectional approach. The study sample used a total sampling technique, namely all students of Angkasa Kindergarten, Surakarta, with a total of 103 children. Research data were obtained from microscopic observations and questionnaire results, which were then then tested using Chi-Square. Of the 81 Anal swab samples, 3,7% were found to be positive for Oxyuris vermicularis eggs and 96,3% were negative for Oxyuris vermicularis eggs. Chi-Square analysis with Fisher’s Exact Test obtained a significant value of 0.043 (p-value <0,05) which is less than 0,05. It can be concluded that there is a significant correlation bettwen handwashing with soap and Oxyuris vermicularis infection in children at Angkasa Kindergarten, Surakarta.